2019
DOI: 10.21608/asnj.2019.56822
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Educational Program on Nurses’performance Regarding Patients with Acute Pancreatitis

Abstract: Background: Acute pancreatitis is the inflammation of the pancreas that results in auto-digestion by its own pancreatic enzymes. The educational program is considered to be an important means to provide nurses with theoretical and technical information needed to acquire skills and competencies necessary to continually improve nursing practice. Objective: Theaim of this study was to evaluate effectof educational program on nurses 'performance regarding patients with acute pancreatitis. Design: A quasi-experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 3 publications
5
0
0
Order By: Relevance
“…Most of patients' records in the post-intervention phase were ranked 3 and above, which reflects improvement. This is in agreement with, Mohammed et al, (2019) who reported that there was statistically significant improvement in nursing staff total mean pancreatic pain score immediately after implementation of the educational program. Regarding the correlation between demographic characteristics and total knowledge score of the studied nurses.…”
Section: The Aim Of This Studysupporting
confidence: 92%
See 4 more Smart Citations
“…Most of patients' records in the post-intervention phase were ranked 3 and above, which reflects improvement. This is in agreement with, Mohammed et al, (2019) who reported that there was statistically significant improvement in nursing staff total mean pancreatic pain score immediately after implementation of the educational program. Regarding the correlation between demographic characteristics and total knowledge score of the studied nurses.…”
Section: The Aim Of This Studysupporting
confidence: 92%
“…This is because the educational guidelines were effective and influential and brought about progress in nurses' practices, and they were needed for an educational program. In the same line, supporting our results Mohammed et al, (2019) who noted that there was statistically significant improvement in nursing staff practice of studied nurses immediately after implementation of the educational program. Regarding total mean score of total pancreatic pain, this result showed that nurses assess the total mean of pancreatic pain and noted reduction from ±SD (23.2±6.8) pre intervention to ±SD (12.52±6.1) and ±SD (3.43±1.53) immediately and after intervention respectively for the study group with statistically high significance difference P= <0.001.…”
Section: The Aim Of This Studysupporting
confidence: 91%
See 3 more Smart Citations